2002
DOI: 10.1021/es025876f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Historic PCB Exposures on the Reproductive Success of the Hudson River Striped Bass Population

Abstract: Scientists and regulatory agencies have expressed concern that exposures to polychlorinated biphenyls (PCBs) might be contributing to reductions in the abundance of fish populations exposed to these chemicals. The specific effects of concern involve impairment of fish reproduction, including both reduced egg production and decreased viability of eggs and larvae. We tested hypotheses concerning the effects of PCBs on fish populations using long-term data sets available for the striped bass population of the Hud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…This finding is consistent with earlier findings (Barnthouse et al 2003), which showed that elevated levels of PCBs had no measurable effect on reproductive success in the Hudson River striped bass population. In the case of striped bass, any effects of PCBs on their reproduction were small compared with the effects of restrictions on striped bass harvests introduced in the mid‐1980s, which led to a 10‐fold increase in the size of the spawning population and in annual egg production, accompanied by a compensatory 90% decline in the survival of striped bass larvae.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with earlier findings (Barnthouse et al 2003), which showed that elevated levels of PCBs had no measurable effect on reproductive success in the Hudson River striped bass population. In the case of striped bass, any effects of PCBs on their reproduction were small compared with the effects of restrictions on striped bass harvests introduced in the mid‐1980s, which led to a 10‐fold increase in the size of the spawning population and in annual egg production, accompanied by a compensatory 90% decline in the survival of striped bass larvae.…”
Section: Discussionsupporting
confidence: 93%
“…As in the case of striped bass (Barnthouse et al 2003), previous inferences concerning effects of PCB exposures on the Hudson River white perch population have been based on conservative interpretations of limited laboratory and field data. The USEPA LOAELTRV was derived from a laboratory study performed by Hansen et al (1974), in which sheepshead minnow ( Cyprinodon variegatus ) fry were exposed to waterborne PCBs during a 28‐d period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCBs declined an order of magnitude since the 1970s in adult striped bass (Morone saxatilis) and white perch (Morone americana) in the lower Hudson River (Albany to New York, New York, USA) and during this time, reproductive success was not related to temporal trends in PCBs (Barnthouse et al, 2003(Barnthouse et al, , 2009. In fact, a positive correlation between maternal lipid-based PCBs in white perch and subsequent abundance at age-1 was observed (Barnthouse et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…When they are, they are usually applied to individual populations, although occasionally they may be applied to a set of populations. They may be measured in the field and exposure-response relationships derived from the field observations may be used to estimate ecological risks (Barnthouse et al 2003). Endpoints based on population attributes are supported by policy and precedent (USEPA 2003).…”
Section: Production Of the Brook Trout Population In Short Creekmentioning
confidence: 99%